Normal-temperature self-repairing polycarbonate and preparation method thereof

By introducing 3,5-dihydroxybenzamide monomer into polycarbonate, the self-healing of room temperature is achieved using double-tooth hydrogen bonds, which solves the problem of irreversible damage to polycarbonate materials in outdoor applications, improves the service life and safety and reliability of the materials, while maintaining high mechanical and heat resistance.

CN119735798AActive Publication Date: 2025-04-01WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411930564.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Polycarbonate materials are prone to scratches, cracks and other damage in outdoor applications. The prior art self-repair methods have problems such as irreversibility, dependence on external energy input and reduced mechanical properties.

Method used

By introducing 3,5-dihydroxybenzamide monomer into polycarbonate, the material is imparted with a normal temperature self-healing function by using bitodental hydrogen bonds, and self-healing is achieved through non-covalent bonds to enhance the mechanical properties of the material.

Benefits of technology

It realizes self-repair of polycarbonate materials at room temperature, with a mechanical repair rate of 70%, improving the service life and safety and reliability of the materials, while maintaining high mechanical and heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735798A_ABST
    Figure CN119735798A_ABST
Patent Text Reader

Abstract

The invention provides normal-temperature self-repairing polycarbonate and a preparation method thereof, the normal-temperature self-repairing polycarbonate has the following structural formula: # imgabs0 #, in which R is a monophenol-derived group; the value of m ranges from 10 to 120, and the value of n ranges from 5 to 80. According to the invention, PC is endowed with a normal-temperature self-healing function by introducing a third monomer with a self-repairing function. According to the prepared self-repairing PC, the service life of the PC is greatly prolonged, self-repairing of cracks can be achieved at the normal temperature (25 DEG C), and the mechanical repairing rate reaches 70%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polycarbonate material capable of self-repairing at room temperature and a preparation method thereof, belonging to the technical field of polymer materials. Background Art

[0002] Polycarbonate (PC), as a high-performance thermoplastic engineering plastic, is widely used in many fields, including the automotive industry, instrumentation, electronic appliances, building materials, etc., due to its high light transmittance, high impact resistance, excellent heat resistance, weather resistance and good electrical insulation properties. However, with the continuous expansion of the application fields of polycarbonate materials, the defects exposed in actual use are becoming increasingly prominent, especially in outdoor applications. Due to the long-term influence of the natural environment and external forces, the surface of polycarbonate products is prone to scratches, cracks and other damages, which seriously affect its performance and service life.

[0003] At present, the problem of surface damage of polycarbonate is mainly improved through surface coating, surface treatment and other methods. However, these methods still have many shortcomings in practical applications. First, although traditional surface coating can improve the wear resistance and scratch resistance of polycarbonate products to a certain extent, when the coating is damaged by a large external force, the damage is often irreversible and cannot be self-repaired. Secondly, although some surface treatment methods can improve the weather resistance and corrosion resistance of polycarbonate products to a certain extent, they often need to be carried out under specific environmental conditions, which is complicated and costly.

[0004] In addition, existing polycarbonate materials often need to be repaired or replaced manually after being damaged, which not only increases maintenance costs but also affects the continuous use performance of the product. Especially in some special fields, such as aerospace and marine engineering, the reliability and durability of materials are extremely high. Once the material is damaged, it may lead to serious consequences.

[0005] In view of the shortcomings of the existing technology, the development of a method for preparing polycarbonate with self-repairing function has important practical significance and application value. First, the self-repairing function can realize the automatic repair of minor damage on the surface of polycarbonate products, extend their service life, reduce the frequency of replacement and maintenance, and thus reduce the cost of use. Secondly, the self-repairing function can improve the reliability and durability of polycarbonate products, especially in some fields with extremely high requirements for material performance, such as aerospace, marine engineering, etc., the self-repairing function will greatly improve the safety and reliability of the products.

[0006] After investigating the existing patents, it was found that Chinese Patent Publication No. CN108699228A discloses a method of introducing disulfide into the main chain to give polycarbonate a self-repairing function, but the introduction of disulfide will greatly reduce the mechanical properties and heat resistance of polycarbonate, and release toxic gases such as sulfur dioxide during processing; U.S. Patent Publication No. US11136433B2 discloses a method of introducing esters and heterocyclic structures into the main chain to give polycarbonate a self-repairing function, but the introduction of flexible structures will cause the strength of polycarbonate to decrease and the scope of application to decrease. In addition, the principles of the above two methods to give polycarbonate a self-repairing function are both reversible covalent bonds with high bond energy, so the realization of self-repair requires external energy input (160°C or strong ultraviolet light irradiation), and it is impossible to essentially eliminate the artificial processing and repair process after the polycarbonate material is damaged.

[0007] Therefore, it is necessary to develop a room-temperature self-healing polycarbonate material that can take into account both mechanical properties. Summary of the invention

[0008] In view of the above problems existing in the prior art, the object of the present invention is to provide a polycarbonate (PC) that can self-repair at room temperature and a preparation method thereof. The present invention imparts the polycarbonate with room temperature self-repairing function through non-covalent bonds, while enhancing the mechanical properties of the polycarbonate.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] The present invention provides a room temperature self-repairable polycarbonate having a structural formula as shown in the following formula (1):

[0011]

[0012] Wherein, R is a group derived from a monophenol, preferably a group derived from p-tert-butylphenol, phenol, m-tert-butylphenol, or methylphenol; m is 10-120, for example, 10, 30, 50, 80, 100, 120, etc., and n is 5-80, for example, 5, 10, 30, 50, 70, 80, etc.

[0013] The present invention also provides a method for preparing the room temperature self-repairable polycarbonate, comprising the following steps:

[0014] 1) mixing bisphenol A, 3,5-dihydroxybenzamide, alkali, hydrosulfite (sodium dithionite) and water to obtain a homogeneous aqueous solution;

[0015] 2) adding an oil-soluble solvent to the homogeneous aqueous solution of step 1) to obtain an oil-water mixture;

[0016] 3) introducing phosgene and alkali solution into the oil-water mixture of step 2) to react;

[0017] 4) adding a catalyst and a monophenol end-capping agent to the reaction system of step 3), and introducing an alkali solution to react;

[0018] 5) The reaction liquid in step 4) is separated into layers, and the oil phase is taken out. After acid washing and water washing, the oil-soluble solvent is removed to obtain PC polycarbonate capable of self-repairing at room temperature.

[0019] In a specific embodiment, the concentration of bisphenol A in the homogeneous aqueous solution in step 1) is 10-20wt%, such as 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, etc.;

[0020] The concentration of the 3,5-dihydroxybenzamide in the homogeneous aqueous solution is 3-13wt%, such as 3wt%, 5wt%, 7wt%, 9wt%, 11wt%, 13wt%, etc.;

[0021] The concentration of the base in the homogeneous aqueous solution is 5-8wt%, such as 5wt%, 6wt%, 7wt%, 8wt%, etc.;

[0022] The concentration of the hydrosulfite in the aqueous solution is 50-300ppm, such as 50ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, etc.;

[0023] Preferably, the homogeneous aqueous solution in step 1) is prepared under an inert atmosphere, such as a nitrogen environment.

[0024] In a specific embodiment, the base in step 1) is a metal hydroxide, preferably one or more of NaOH and KOH.

[0025] In a specific embodiment, the oil-soluble solvent in step 2) is selected from one or more of dimethylacetamide (DMF), chloroform, tetrachloroethane, dichloromethane, chlorobenzene, tetrahydrofuran, dioxane, and pyridine.

[0026] In a specific embodiment, the mass ratio of the homogeneous aqueous solution to the oil-soluble solvent in step 2) is 0.5-2, for example, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, etc., preferably 0.8-1.5.

[0027] In a specific embodiment, the molar ratio of the phosgene in step 3) to the bisphenol A in step 1) is 1-3, for example, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, etc.;

[0028] Preferably, the rate at which phosgene is introduced into the reaction system is 0.8-2.5 L / min, for example, 0.8 L / min, 1 L / min, 1.2 L / min, 1.5 L / min, 1.8 L / min, 2 L / min, 2.2 L / min, 2.5 L / min, etc.

[0029] In a specific embodiment, step 3) continuously introduces the alkali solution during the reaction, and the rate of introducing the alkali solution into the reaction system is 1-15 g / min, such as 1 g / min, 3 g / min, 5 g / min, 7 g / min, 9 g / min, 11 g / min, 13 g / min, 15 g / min, etc.; the alkali solution is continuously introduced during the reaction until the introduction of phosgene is completed;

[0030] Preferably, the alkali solution is an aqueous solution of alkali, and the concentration is 5-45wt%, such as 5wt%, 15wt%, 25wt%, 35wt%, 45wt%, etc., preferably 32-40%;

[0031] Wherein, the base is a metal hydroxide, preferably one or more of strong bases such as NaOH and KOH, and more preferably NaOH.

[0032] In a specific embodiment, the reaction in step 3) is carried out at a temperature of 20-36°C, for example, 20°C, 22°C, 25°C, 28°C, 30°C, 33°C, 35°C, 36°C, etc., and the reaction time is 5-10 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, etc.

[0033] In a specific embodiment, the amount of the catalyst added to the reaction solution in step 4) is 50-800 ppm, such as 50 ppm, 100 ppm, 200 ppm, 400 ppm, 600 ppm, 800 ppm, etc.;

[0034] The amount of the monophenol added to the reaction solution is 1500-3000 ppm, for example, 1500 ppm, 1700 ppm, 2000 ppm, 2200 ppm, 2500 ppm, 2800 ppm, 3000 ppm, etc.

[0035] In a specific embodiment, the monophenol used as the end-capping agent in step 4) is selected from one or more of p-tert-butylphenol, phenol, m-tert-butylphenol, methylphenol, etc., preferably p-tert-butylphenol and / or phenol.

[0036] In a specific embodiment, the catalyst in step 4) is triethylamine or a quaternary ammonium salt compound, preferably one or more of triethylamine, N,N,N,N-trimethylbenzylammonium chloride, N,N,N,N-dimethylethyloctadecylammonium sulfate, more preferably triethylamine.

[0037] In a specific embodiment, the alkali solution in step 4) is introduced in an amount of 0.4-1% of the mass of the reaction system, such as 0.4%, 0.6%, 0.8%, 1%, etc., based on the alkali therein;

[0038] Preferably, the alkali solution is an aqueous solution of alkali, and the concentration is 25-45wt%, such as 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, etc., preferably 30-40wt%;

[0039] Wherein, the base is a metal hydroxide, preferably one or more of strong bases such as NaOH and KOH, and more preferably NaOH.

[0040] In a specific embodiment, the reaction in step 4) is carried out at a temperature of 25-38°C, for example, 25°C, 28°C, 30°C, 33°C, 35°C, 36°C, 38°C, etc., and the reaction time is 5-40 min, for example, 5 min, 10 min, 20 min, 30 min, 40 min, etc.

[0041] In a specific embodiment, step 5) includes operations such as stratification, pickling, water washing, and desolventizing, which are all conventional treatment methods in the field and are not specifically required by the present invention. Specifically, the pickling is to use an acid-water solution to wash the oil phase, wherein the acid can be one or more of strong acid substances such as hydrochloric acid, sulfuric acid, and nitric acid, preferably hydrochloric acid; preferably, the acid-water solution has a concentration of 0.5wt%-10wt%, preferably 0.9wt%; the water washing is performed until the water phase after washing is neutral and the conductivity is less than 100μS / cm.

[0042] The room temperature self-repairable PC polycarbonate solid product prepared by the method described above in the present invention has a catalyst content of less than 0.5 ppm, a chloride ion content of less than 8 ppm, and an oil-soluble solvent content of less than 200 ppm.

[0043] Compared with the prior art, the present invention has the following advantages:

[0044] 1) A PC material that can self-repair at room temperature was prepared. It can achieve self-repair of cracks at room temperature (25°C), with a mechanical repair rate of 70%, which greatly improves the service life of PC and greatly improves the safety, reliability and service life of PC.

[0045] 2) The PC material is endowed with room-temperature self-repairing properties by adding 3,5-dihydroxybenzamide monomers and using bidentate hydrogen bonds (the self-repairing mechanism is shown in the following formula). After a crack appears, it only needs to apply pressure on both sides of the fracture to achieve efficient self-repair.

[0046]

[0047] 3) Compared with the prior art, the present invention is the first to create a PC that can self-repair at room temperature and optimizes the molecular structure of PC. Compared with the self-repairable PC prepared using monomers containing reversible covalent bond structures, the advantages are: first, the conditions for completing self-repair are more extensive, and efficient self-repair can be achieved without external energy input (heating or light); second, the mechanical properties of PC are improved, and the tensile strength of PC is improved through structural optimization; third, the heat resistance of PC is improved, and the high-density bidentate hydrogen bonds will absorb heat during the PC processing process to prevent PC from overheating and degradation. DETAILED DESCRIPTION

[0048] The present invention is further described in detail below through specific examples. The examples of the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0049] In the embodiments and comparative examples of the present invention, the sources of the main raw materials used are as follows. Unless otherwise specified, other raw materials and reagents were purchased from commercial sources:

[0050] Bisphenol A: purchased from McLean, product number B802575-500g;

[0051] 3,5-Dihydroxybenzamide: purchased from McLean, product number D859848-25g;

[0052] Sodium hydroxide: purchased from Maclean, product number S832169;

[0053] Phosgene: refer to Zhou Yiping's "Improvement of Phosgene Preparation Method";

[0054] p-tert-Butylphenol: purchased from Maclean, product number B802759;

[0055] Triethylamine: purchased from McLean, product number T818774;

[0056] Dichloromethane: purchased from McLean, product number D807826;

[0057] Hydrosulfite: purchased from McLean, item number S817916.

[0058] [Example 1]

[0059] Preparation of room temperature self-healing polycarbonate (sample 1# -4 # ):

[0060] 1) Add 700 ml of pure water to a 3L jacketed reactor under nitrogen protection, start stirring, and then add 40 g of solid NaOH until it is completely dissolved. After cooling to room temperature, add 1.5 g of sodium hydrosulfite, 100 g of bisphenol A solid, and add 30 g, 40 g, 50 g and 60 g of 3,5-dihydroxybenzamide solid according to samples 1#-4#, respectively, and continue stirring until the solid is completely dissolved to obtain 1#-4# homogeneous aqueous solutions;

[0061] 2) To 1 # -4 # Add 850 g of dichloromethane to the homogeneous aqueous solution, and stir to mix the aqueous phase and the oil phase evenly to obtain an oil-water mixture;

[0062] 3) 12.3 L of phosgene was introduced into the reactor at a rate of 1.23 L / min, and a 32 wt% NaOH aqueous solution was added into the reactor at a rate of 2.4 g / min until the introduction of phosgene was completed, during which the reaction temperature was controlled at 35.5° C. and the reaction was carried out for 10 min;

[0063] 4) adding 94 ppm of triethylamine and 1800 ppm of p-tert-butylphenol to the reaction mixture in the reactor, and adding 32 wt % of NaOH aqueous solution to the reactor, wherein the amount of NaOH therein is 0.6 wt % of the mass of the reaction mixture, and stirring the reaction for 30 min, during which the reaction temperature is controlled at 36-38 ° C;

[0064] 5) After the water and oil phases were separated, the oil phase was first washed with a 1.5 wt % HCl aqueous solution according to an appropriate water-oil ratio, and then the oil phase was washed with pure water until the water phase after washing was neutral and the conductivity was less than 100 μS / cm, and then the dichloromethane was removed and dried to obtain a room temperature self-healing polycarbonate solid (i.e., sample 1 # -4 # );

[0065] The structure of the room temperature self-repairable polycarbonate prepared in this embodiment is:

[0066] Add 30 g 3,5-dihydroxybenzamide (Sample 1 # ):

[0067]

[0068] Add 40 g 3,5-dihydroxybenzamide (Sample 2 # ):

[0069]

[0070] Add 50 g of 3,5-dihydroxybenzamide (Sample 3 # ):

[0071]

[0072] Add 60 g of 3,5-dihydroxybenzamide (Sample 4 # ):

[0073]

[0074] Characterization: The prepared room temperature self-healing polycarbonate was analyzed by nuclear magnetic resonance hydrogen spectrum, proving that 3,5-dihydroxybenzamide participated in the polymerization and entered the polymer main chain; the specific analysis results are 1 H NMR (CDCl3, 500MHz): δ7.89-8.11(m,2H),7.55(s,1H),7.50(s,2H),7.09-7.35(m,8H),1.66(s,6H).

[0075] Room temperature self-healing polycarbonate (sample 1 # -4 # ) performance test, the results are shown in Table 1 below:

[0076] Prepare sample plates according to GB / T 35513.2-2017 and analyze heat resistance (ΔYI);

[0077] According to GB / T 1040-1992, tensile specimens were prepared. A scratch with a depth of 1 mm was made in the middle of the neck using a blade. The tensile strength was tested immediately. The tensile specimens that had undergone the same scratching treatment were artificially squeezed at room temperature (25°C) for 15 minutes, and then the tensile strength was tested. The repair rate was calculated based on the tensile strength of the unscratched tensile specimens.

[0078] Table 1 Sample 1 # -4 # Performance Test Results

[0079]

[0080] [Example 2]

[0081] Preparation of room temperature self-healing polycarbonate (sample 5 # -7 # ):

[0082] 1) Add 700 ml of pure water to a 3L jacketed reactor under nitrogen protection, start stirring, and then add 40 g of solid NaOH until it is completely dissolved. After cooling to room temperature, add 1.5 g of hydrosulfite, 100 g of bisphenol A solid, and 30 g of 3,5-dihydroxybenzamide solid, and continue stirring until the solid is completely dissolved to obtain a homogeneous aqueous solution.

[0083] 2) adding 850 g of dichloromethane to the homogeneous aqueous solution, stirring to make the aqueous phase and the oil phase mix evenly to obtain an oil-water mixture;

[0084] 3) 10.3 L of phosgene was introduced into the reactor at a rate of 1.23 L / min, and 32 wt% NaOH solution was added into the reactor at a rate of 2.4 g / min until the introduction of phosgene was completed, during which the reaction temperature was controlled at 35.5° C. and the reaction was carried out for 8 min;

[0085] 4) Add 94 ppm of triethylamine to the reaction solution, and repeat the above steps to add 1% triethylamine to three reaction kettles according to sample 5. # -7 # 1800ppm, 2400ppm and 3000ppm of p-tert-butylphenol were added, and at the same time, 32wt% NaOH aqueous solution was added to the reactor, with the amount of NaOH being 0.6% of the mass of the reaction solution, and the reaction was stirred for 30min, during which the reaction temperature was controlled at 36-38°C;

[0086] 5) After the water and oil phases are separated, the oil phase is first washed with a 1.5% HCl solution according to an appropriate water-oil ratio, and then the oil phase is washed with pure water until the water phase after washing is neutral and the conductivity is less than 100 μS / cm, and then the dichloromethane is removed and dried to obtain a room temperature self-healing polycarbonate solid (i.e., sample 5). # -7 # );

[0087] The structure of the room temperature self-repairable polycarbonate prepared in this embodiment is:

[0088] Add 1800ppm of p-tert-butylphenol (sample 5 # ):

[0089]

[0090] Add 2400ppm of p-tert-butylphenol (Sample 6 # ):

[0091]

[0092] Add 3000ppm of p-tert-butylphenol (sample 7 # ):

[0093]

[0094] Characterization: The prepared room temperature self-healing polycarbonate sample 5 # -7 # Using GPC analysis, the weight average molecular weight of the polymer decreases as the amount of p-tert-butylphenol added increases; the specific data are shown in Table 2 below:

[0095] Table 2 Sample 5 # -7 # Weight average molecular weight

[0096] sample Addition amount of tert-butylphenol Weight average molecular weight <![CDATA[5 # ]]> 1800ppm 42600 <![CDATA[6 # ]]> 2400ppm 31850 <![CDATA[7 # ]]> 3000ppm 24960

[0097] The room temperature self-healing polycarbonate (sample 5) was prepared in the same manner as in Example 1. # -7 # ) to perform performance testing, the results are shown in Table 3 below:

[0098] Table 3 Sample 5 # -7 # Performance Test Results

[0099]

[0100] The data in Tables 2 and 3 prove that the self-repairing ability of the room temperature self-repairing polycarbonate of the present invention will not change due to changes in molecular weight.

[0101] Example 3

[0102] According to the method of sample 1# in Example 1, the p-tert-butylphenol was replaced with an equal amount of phenol, and other operations and conditions remained unchanged to obtain a room temperature self-healing polycarbonate solid (i.e., sample 8 # )

[0103] The performance of polycarbonate was tested in the same manner as in Example 1. The results are shown in Table 4 below:

[0104] Table 4 Sample 8 # Performance Test Results

[0105]

[0106] Comparative Example 1

[0107] Polycarbonate was obtained by following the method of Example 1 except that 3,5-dihydroxybenzamide was not added in step 1) and other operations and conditions remained unchanged.

[0108] The performance of polycarbonate was tested in the same manner as in Example 1. The results are shown in Table 5 below:

[0109] Table 5 Performance test results

[0110]

[0111] Comparative Example 2

[0112] Polycarbonate was prepared according to the method of Example 1, except that 3,5-dihydroxybenzamide was replaced with 3,5-dihydroxyacetophenone (McLean, product number D829137) in step 1), and other operations and conditions remained unchanged.

[0113] The performance of polycarbonate was tested in the same manner as in Example 1. The results are shown in Table 6 below:

[0114] Table 6 Performance test results

[0115]

[0116]

Claims

1. A room temperature self-repairable polycarbonate having the structural formula shown in the following formula (1): in, R is a group derived from a monophenol, preferably a group derived from p-tert-butylphenol, phenol, m-tert-butylphenol, or methylphenol; m is 10-120, and n is 5-80.

2. A method for preparing the room temperature self-repairable polycarbonate, characterized in that: The following steps are involved: 1) mixing bisphenol A, 3,5-dihydroxybenzamide, alkali, hydrosulfite and water to obtain a homogeneous aqueous solution; 2) adding an oil-soluble solvent to the homogeneous aqueous solution of step 1) to obtain an oil-water mixture; 3) introducing phosgene and alkali solution into the oil-water mixture of step 2) to react; 4) adding a catalyst and a monophenol end-capping agent to the reaction system of step 3), and introducing an alkali solution to react; 5) The reaction liquid in step 4) is separated into layers, and the oil phase is taken out. After acid washing and water washing, the oil-soluble solvent is removed to obtain PC polycarbonate capable of self-repairing at room temperature.

3. The preparation method according to claim 1, characterized in that: Step 1) The concentration of bisphenol A in the homogeneous aqueous solution is 10-20 wt %; The concentration of the 3,5-dihydroxybenzamide in the homogeneous aqueous solution is 3-13 wt %; The concentration of the base in the homogeneous aqueous solution is 5-8wt%; The concentration of the hydrosulfite in the aqueous solution is 50-300 ppm; and / or In step 1), the base is a metal hydroxide, preferably one or more of NaOH and KOH.

4. The preparation method according to claim 1, characterized in that: Step 2) the oil-soluble solvent is selected from one or more of dimethylacetamide, chloroform, tetrachloroethane, dichloromethane, chlorobenzene, tetrahydrofuran, dioxane, and pyridine; and / or In step 2), the mass ratio of the homogeneous aqueous solution to the oil-soluble solvent is 0.5-2, preferably 0.8-1.

5.

5. The preparation method according to claim 1, characterized in that: The molar ratio of the phosgene in step 3) to the bisphenol A in step 1) is 1-3; Preferably, the rate at which phosgene is introduced into the reaction system is 0.8-2.5 L / min.

6. The preparation method according to claim 1, characterized in that: Step 3) continuously introducing the alkali solution during the reaction, wherein the rate of introducing the alkali solution into the reaction system is 1-15 g / min; continuously introducing the alkali solution during the reaction until the introduction of phosgene is completed; Preferably, the alkali solution is an aqueous solution of alkali with a concentration of 5-45wt%, preferably 32-40%; Wherein, the alkali is a metal hydroxide, preferably one or more of NaOH and KOH, more preferably NaOH.

7. The preparation method according to claim 1, characterized in that: In step 3), the reaction temperature is 20-36° C. and the reaction time is 5-10 min.

8. The preparation method according to claim 1, characterized in that: Step 4) The amount of the catalyst added to the reaction solution is 50-800 ppm; The monophenol is added in an amount of 1500-3000 ppm in the reaction solution; and / or Step 4) the monophenol is selected from one or more of p-tert-butylphenol, phenol, m-tert-butylphenol, and methylphenol, preferably p-tert-butylphenol and / or phenol; and / or Step 4) The catalyst is triethylamine or a quaternary ammonium salt compound, preferably one or more of triethylamine, N,N,N,N-trimethylbenzylammonium chloride, N,N,N,N-dimethylethyloctadecylammonium sulfate, more preferably triethylamine.

9. The preparation method according to claim 1, characterized in that: Step 4) the alkali solution is introduced in an amount of 0.4-1% of the mass of the reaction system, calculated as the alkali therein; Preferably, the alkali solution is an aqueous solution of alkali with a concentration of 25-45wt%, preferably 30-40wt%; Wherein, the alkali is a metal hydroxide, preferably one or more of NaOH and KOH, more preferably NaOH.

10. The preparation method according to claim 1, characterized in that: In step 4), the reaction temperature is 25-38° C. and the reaction time is 5-40 min.

Citation Information

Patent Citations

  • Inherently healing polycarbonate resins

    CN108699228A

  • Self-healing copolymerized polycarbonate and preparation method therefor

    US11136433B2

  • Self-repairing polyurethane elastomer containing sextuple intermolecular hydrogen bonds and preparation method of self-repairing polyurethane elastomer

    CN113831493A

  • Self-healing PC (polycarbonate) material as well as preparation method and application thereof

    CN115926063A

  • Self-repairable urethane (METH)acrylamide and resin composition containing the same

    JP2020100821A